Single-case experimental designs to assess intervention effectiveness in rehabilitation: A practical guide - Krasny-Pacini, Agata; Evans, Jonathan (Annals of physical and rehabilitation medicine, 2018)
Single-case experimental designs (SCED) are experimental designs aiming at testing the effect of an intervention using a small number of patients (typically one to three), using repeated measurements, sequential (±randomized) introduction of an intervention and method-specific data analysis, including visual analysis and specific statistics. The aim of this paper is to familiarise professionals working in different fields of rehabilitation with SCEDs and provide practical advice on how to design and implement a SCED in clinical rehabilitation practice. Research questions suitable for SCEDs and the different types of SCEDs (e.g., alternating treatment designs, introduction/withdrawal designs and multiple baseline designs) are reviewed. Practical steps in preparing a SCED design are outlined. Examples from different rehabilitation domains are provided throughout the paper. Challenging issues such as the choice of the repeated measure, assessment of generalisation, randomization, procedural fidelity, replication and generalizability of findings are discussed. Simple rules and resources for data analysis are presented. The utility of SCEDs in physical and rehabilitation medicine (PRM) are discussed.